1986
DOI: 10.1177/036354658601400305
|View full text |Cite
|
Sign up to set email alerts
|

Followup of the acute nonoperated isolated anterior cruciate ligament tear

Abstract: This report is an attempt to analyze what happens to an isolated ACL tear that is treated nonoperatively. The results of 40 patients treated initially by nonoperative means for this injury and followed an average of 4 years are reported. A very small percentage of these patients had associated meniscal pathology. Secondary reconstructive surgery was necessary in 12 patients (30%). Primary meniscal tears were present in 4 of 25 knees (16%) and secondary meniscal tears occurred in an additional four of the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
137
0
6

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(146 citation statements)
references
References 19 publications
3
137
0
6
Order By: Relevance
“…The higher participation of the population in sports has resulted in a constantly increasing incidence of ACL tears. The func-tional instability after the rupture can lead to additional meniscal and chondral injuries as well as to the development of degenerative joint disease [9,15,16,22]. Successful treatment must therefore preserve intact meniscal and chondral structures.…”
Section: Introductionmentioning
confidence: 99%
“…The higher participation of the population in sports has resulted in a constantly increasing incidence of ACL tears. The func-tional instability after the rupture can lead to additional meniscal and chondral injuries as well as to the development of degenerative joint disease [9,15,16,22]. Successful treatment must therefore preserve intact meniscal and chondral structures.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of this support mechanism changes the joint kinematics and induces joint instability and osteoarthritic changes [10,17]. However, Kennedy et al [12] reported in 1982 that clinical symptoms characteristic of knees with ACL injury (e.g., giving way, progressive laxity, and early degenerative changes) occur due to the disappearance of mechanoreceptor feedback in addition to altered kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Injury to the ACL often leads to the development of degenerative osteoarthritis (OA) [8,17]. In addition, patients with ACL injury and posttraumatic OA are on average 15-20 years younger than patients with primary OA when they become symptomatic [5,17].…”
Section: Introductionmentioning
confidence: 99%